PS02.153: HER2 PATHWAY CONTROL SENSITIVITY TO CISPLATIN IN ESOPHAGEAL ADENOCARCINOMA CELL LINES. (14th September 2018) - Dakpo, Eugenia; Derouet, Mathieu; Yeung, Jonathan; Darling, Gail
Abstract: Background: Adenocarcinoma of the esophagus is increasing in frequency and is the 6th most common cause of cancer death in North America. Cisplatin has been the backbone of neoadjuvant therapy but despite improved 5-year survival with neoadjuvant chemoradiation, many tumor cells survive chemotherapy leading to distant metastases. This study investigated the molecular changes in tumors when they become cisplatin resistant by focussing on the HER family of proteins. Methods: We created 2 cisplatin resistant cell lines and a matching control by exposing the adenocarcinoma cell lines SK-GT-4 and FLO-1 to repeated cycles of cisplatin. Resistance to cisplatin was assessed at the end of the treatment. The expression levels of the HER family members was assessed. Cell proliferation, resistance to cisplatin and siRNA transfection were used to assess the role of HER family members in cisplatin resistance in EAC. Results: The cisplatin resistant cell line displayed a lower rate of proliferation than the matching control (1.5 fold difference after 72h, P < 0.05). When the level of HER family members in the cisplatin resistant and control cell lines were measured, we observed a downregulation of HER2 in both cisplatin resistant cell lines (FLO-1: 78.31 mean expression (control) vs 17.43 mean expression (cisplatin resistant), P < 0.05), whereas the EGFR level were unchanged (FLO-1: 154.76 mean expression (control) vs 137.64 mean expression (cisplatin resistant), P > 0.05). In order to confirm this observation, we downregulated HER2 by siRNA and by a HER2 specific inhibitor in control cells. Resistance to cisplatin was similar to the cisplatin resistant cell lines (3.33μM cisplatin for 72h, death rate: 72.1% control vs 23.6% HER2 siRNA, P < 0.05). Similar results were observed in two other EAC cell lines (OE33 And JHESO-AD1). Conclusion: Our results suggest that there is a correlation between HER2 level/activity and cisplatin resistance in EAC cells. It appears that as EAC cells acquire cisplatin resistance, they block the HER2 pathway. Disclosure: All authors have declared no conflicts of interest.